Musa Paradisiaca It's Phytochemistry, Traditional Uses And Pharmacological Activities - Kavita Narayan Gaisamudre (Sarwade),; Prakash Pralhad Sarwade,; Kalpana Sonwani,; Subhash Chand,; Mamta Goswami,; Harpreet Kaur,; Navin Chandra Pant, (Asian Journal of Pharmaceutical Research and Development, 2025)
Musa paradisiaca is a medicinally valuable and plentiful nutritious plant that has been popularly used in the traditional medicine systems of Asia, Africa and Latin America. The bioactive phytochemicals are very diverse in all parts of this plant such as the fruit, peel, leaves, pseudostem, and the flowers which contain phenolic acids, flavonoids, carotenoids, sterols, triterpenes, alkaloids and dietary fibers. A combination of all these constituents contributes to the plant possessing many pharmacological attributes. The review is an analytical study of the phytochemistry, ethnomedicinal use, mechanism of action, and therapeutic potential of Musa paradisiaca. It is established that the plant possesses great anti-inflammatory and antioxidant effects through Nrf2 activation, NF-kB and free radical scavenging. It possesses antidiabetic effects due to inhibition of a-amylase and a-glucosidase, enhancement of insulin sensitivity, and b-cells in the pancreas. The other drug effects are antimicrobial, anticancer, gastroprotective, hepatoprotective, cardioprotective, neuroprotective, nephroprotective, wound healing and reproductive health as shown in several preclinical studies. Despite the promising outlook of the bioactivity, some significant gaps in research include lack of standardization of the extracts, lack of sufficient mechanistic understanding, limited ability to carry out toxicological assessment and lack of well-designed clinical trials. Future studies should focus on the regions of additional phytochemical characterization, the isolation of the active molecules, nanotechnology-based delivery systems, and clinical validation as a form of therapeutic translation. Overall, Musa paradisiaca is a highly diverse plant that has huge potential of becoming useful in terms of being used as useful functional food, nutraceutical, and phytopharmaceutical. Scientific evidence will also need to be developed further and any research gaps will need to be addressed so as to ensure the full medicinal and industrial potential of it is unlocked.